Implementation of Healthy Village in The KP-KAS Program in Preventing Maternal and Child Mortality Rate in Sidotopo Semampir Surabaya - Ronal Surya; lilis ardini; Mia Ika Rahmawati; Wiwiek Srikandi Shabrie; Marsudi Lestariningsih; Nihayatul Munaa (Institute of Computer Science (IOCS), 2020)
This article aims to evaluate the implementation of healthy villages in the KP-KAS program, especially on indicators of efforts to prevent maternal and child mortality. This study uses a qualitative method with an interpretive approach to studying the object of research in more detail. In-depth interviews were conducted with several key informants. The results of this study show that there are several programs carried out in healthy villages to reduce maternal and child mortality, namely eradication malnutrition, vaccination, delivery assisted by health workers, and reproduction health through contraception.